Community awareness, perceptions, and management practices related to pre-eclampsia: An exploratory qualitative study in Mbale City, Eastern Uganda - Enid Kawala Kagoya; Allan G. Nsubuga; Irene Atuhairwe; Prossy Nakattudde; Catherine Asiimwe; Chrispus Gidudu; Elizabeth Ajalo; Paul Waako; Julius Wandabwa; Lawrence Arach; Grace Mbabazi Atwakire; Milton Musaba; et al. (PLoS ONE, 2026)
Background Pre-eclampsia and other hypertensive disorders of pregnancy are the second leading cause of maternal mortality globally, with 95% of deaths occurring in low- and middle-income countries. In Uganda, these conditions account for approximately 16% of maternal deaths. Despite their burden, little is known about women’s knowledge, perceptions, and management practices regarding pre-eclampsia in such settings, yet early recognition and care-seeking are critical to improving outcomes. Objective To explore community awareness, perceptions, and management practices related to pre-eclampsia in Mbale City, Eastern Uganda. Methods An exploratory qualitative study was conducted through face-to-face interviews with 81 women aged 18-49 years during a community outreach event on pre-eclampsia. Data was collected over six days (21 st -26th May 2024) by 28 trained research midwives stationed at various community sites. Interviews were audio-recorded, transcribed, and thematically analyzed using ATLAS.ti software. Results Participants exhibited limited and mixed understanding of pre-eclampsia, often associating it with symptoms such as swollen feet, headaches, body weakness, and high blood pressure, but also with misconceptions such as witchcraft, marital stress, and multiple pregnancies. Many lacked a local term for the condition. Women reported varied care-seeking responses, with some turning to traditional birth attendants and herbal remedies, while others sought biomedical care. Fear of death was a motivator for some to seek timely medical attention. Conclusion There was a critical gap in accurate knowledge and awareness of pre-eclampsia among women in Mbale City. Misconceptions and reliance on traditional remedies contribute to delayed care-seeking. Targeted, culturally appropriate educational interventions are urgently needed to improve early recognition, promote biomedical care, and enhance maternal and newborn outcomes.